Design and optimisation of magnetically-tunable hybrid piezoelectric-triboelectric energy harvester - Satish Rao Ganapathy (Nature Portfolio, 2021)
Abstract The demand for energy harvesting technologies has been increasing over the years that can be attributed to its significance to low power applications. One of the key problems associated with the available vibration-based harvester is the maximum peak power can only be achieved when the device frequency matches the source frequency to generate low usable power. Therefore, in this study, a magnetically-tunable hybrid piezoelectric-triboelectric energy harvester (MT-HPTEH) was designed and optimised. Four key design factors: mass placement, triboelectric surface area, extension length and magnetic stiffness were investigated and optimised. The voltage generation from piezoelectric and triboelectric mechanisms was determined individually to understand the effect of each design factor on the mechanisms. An output power of 659 µW at 180 kΩ at 44 Hz was obtained from the optimised MT-HPTEH with a theoretical–experimental discrepancy of less than 10%. The added magnetically-tunable feature enabled the harvester to work at the desired frequency range with an open circuit voltage between 7.800 and 20.314 V and a frequency range from 38 to 54 Hz. This MT-HPTEH can power at least six wireless sensor networks and can be used for low power applications such as RFID tags. Future work may include designing of energy-saving and sustainable harvester.